PENGARUH PEMBIAYAAN USAHA TERHADAP PENINGKATAN PENDAPATAN NASABAH PADA PEGADAIAN DI KOTA TARAKAN - Darmawati; M.Faisal Abdullah (Jurnal Ilmu Ekonomi JIE, 2019)
This study aimed to analyze the effect of financing for creative and creative business influencing customer income. The type of this research was quantitative method, the data needed was primary data from the results of the customers’ questionnaire of PT. Pawnshop. The data analysis technique was multiple regression analysis techniques. The independent variable used in this study was Krasida Creation and Financing Financing has an effect simultaneously and together on the dependent variable, namely Pegadaian Customer Income, which was in accordance with the theory and previous research. Then from the data obtained for the F test it can be concluded that H0 was rejected and H1 was accepted, which means that the independent variables, Creation and Krasida simultaneously influence and together on the dependent variable, namely Customer Income R-Square 49%